CONTRIBUTION OF AGROFORESTRY SYSTEM IN MAINTAINING CARBON STOCKS AND REDUCING EMISSION RATE AT JANGKOK WATERSHED, LOMBOK ISLAND - markum, markum; Ariesoesiloningsih, Endang; Suprayogo, Didik; Hairiah, Kurniatun (AGRIVITA, Journal of Agricultural Science, 2013)
Agroforestry systems under rules of community-based forest management support local livelihoods in  the Jangkok watershed, Lombok Island. One of the conditions from the forest authoritiesfor allowing  agroforestry system is that it should maintain forest conditions. Since 1995 the Jangkok watershed has undergone rapid land use change, especially in the forest area. These changes led to a reduction of carbon stocks and thus to emission of CO2. This research aimed to: (1) Measure the carbon stocks in several land use system within the Jangkok watershed, (2) Assess the contribution of agroforestry systems in maintaining carbon stocks and reducing emissions. The assesment was performed based on the RaCSA (Rapid Carbon Stock Appraisal) method using three phases: (1) Classify land use change applying TM5 Landsat Satellite images for the period 1995-2009, (2) Measure carbon stock in the main  land uses identified, (3) Quantify the contribution of agroforestry practices. Results showed that (1) The total amount of carbon stock at Jangkok watershed (19,088ha) was 3.69 Mt (193 Mg ha-1); about 23% of this stock found in the agroforestry systems (32% of the area),(2) Gross CO2 emission from the Jangkok watershed was 8.41 Mg ha-1 yr-1, but due to the net gain in agroforestry of 2.55 Mg ha-1 yr-1 the net emission became 5.86 Mg ha-1 yr-1   Keywords:  agroforestry, carbon stocks, carbon emission rate